2016
DOI: 10.5539/gjhs.v8n12p190
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Correlation between Echocardiographic Findings and Serum Ferritin in Thalassemia Major Patients

Abstract: Introduction: Thalassemia is a disorder that affects beta globin gene production and the resultant need for erythrocyte transfusions puts the patient at risk for iron loading, especially cardiac iron loading. Cardiac complications are the most serious ones accompanied by morbidity and mortality. The most harm to the heart is caused by iron overload. Ferritin is generally associated with the amount of stored iron in the body. The aim of this study was to investigate the relationship between echocardiographic fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…There was no statistically significant relationship between serum ferritin level and echocardiographic findings. Similarly, in studies conducted by Bazrgar (10), Ashena (12), Moghaddar (25) and Salari (26) and there was no significant relationship between ferritin levels and echocardiographic findings and diastolic dysfunction, which could be due to low sample size or low age of the research subjects. However, in the studies conducted by Bosi G et al (27) and the study conducted by Gharzuddine (11), a weak and significant relationship was found between them.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…There was no statistically significant relationship between serum ferritin level and echocardiographic findings. Similarly, in studies conducted by Bazrgar (10), Ashena (12), Moghaddar (25) and Salari (26) and there was no significant relationship between ferritin levels and echocardiographic findings and diastolic dysfunction, which could be due to low sample size or low age of the research subjects. However, in the studies conducted by Bosi G et al (27) and the study conducted by Gharzuddine (11), a weak and significant relationship was found between them.…”
Section: Discussionmentioning
confidence: 80%
“…In the study conducted by Yuksel et al, the ferritin level above 2500 was associated with cardiac complications (19). In the study conducted by Moghaddar et al, the mean serum ferritin level was 2419.13 ± 1772.65 (25). In the study conducted by Faruqi et al, the mean ferritin level was 6062.61 ± 3641.79 (21).…”
Section: Discussionmentioning
confidence: 95%
“…According to Das et al (13) , patients who had greater blood ferritin levels had larger LVDs and worse EF. A few investigations, like those by Usha et al (14) and Khalilian et al (15) , found no statistically significant relationship between blood ferritin levels and echocardiographic parameters. This could be explained by different study population number (being lower in their studies) and different cut off values of s. ferretin used in their studies (being higher in their studies), which may lead to iron overload in cardiac muscle and iron toxicity.…”
Section: Discussionmentioning
confidence: 91%